Darknet : geopolitics and uses - Gayard, Laurent (London [UK] : ISTE Ltd ; Hoboken, NJ, USA : John Wiley & Sons, Inc., 2018)
This collaborative research project allows for fundamental advances not only in the understanding of the phenomena but also in the development of practical calculation methods that can be used by engineers. This collaborative research project allows for fundamental advances not only in the understanding of the phenomena but also in the development of practical calculation methods that can be used by engineers.
New Frontiers and Governance of Digital Space. New Frontiers and Governance of Digital Space -- Fragmentation and Compartmentalization of Virtual Space -- A Society of Control and Panopticism -- The Internet, a Governance Subject to Controversy -- Crypto-Anarchism, Cryptography and Hidden Networks. Crypto-Anarchism, Cryptography and Hidden Networks -- From the ARPANET to the Darknet: When States Lose Cryptographic Warfare -- From Sneaker Nets to Darknets -- Geopolitics and Cybersecurity -- Conclusion -- Declaration of Independence of Cyberspace (John P. Barlow, February 1996) -- Digital Gangster Manifesto.
Includes bibliographical references and index.
Online resource, title from digital title page (viewed on May 19, 2020).
John Wiley and Sons
Keywords: Internet; Internet -- Law and legislation; Internet -- Government policy; World Wide Web; Internet; Internet -- Politique gouvernementale; Web; Internet; World Wide Web; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Internet; Internet -- Government policy; Internet -- Law and legislation; World Wide Web